Characteristics and formation mechanism of seafloor domes on the north‐eastern continental slope of the South China Sea. (28th November 2018) - Wu, Tingting; Wei, Jiangong; Liu, Shengxuan; Guan, Yongxian; Zhang, Ruwei; Su, Ming; Wang, Hongbin; Zhang, Wei; Meng, Dajiang; Liu, Bin
Abstract : Multibeam echo‐sounding and seismic data were obtained during three geophysical surveys by Guangzhou Marine Geological Survey (GMGS) on the north‐eastern slope of the South China Sea (SCS). Nineteen seafloor domes and numerous elongated pockmarks were distinguished in the study area. The seafloor domes vary on number of summits, shape, and spatial interrelation, based on which they were classified into four types which are single‐summit, double‐summits, elongated, and connected. Bottom simulating reflectors and blanking zone underneath were observed in the seismic profiles, indicating the potential existence of gas hydrate and free gas. Multiple faults and diapirs exist beneath the seafloor domes and pockmarks, which were inferred to provide efficient pathways for fluid migrating from deep subsurface. The seafloor domes exhibits high backscatter feature, which is potentially associated with the seep‐related gas hydrate and authigenic carbonate in the shallow sediment. It is speculated that fault and diapir activity, fault sliding caused by region extension and the interaction between neighbour domes control and affect the activity and formation of the domes. However, further investigations, including geological sampling and seafloor observation, are still needed to confirm whether they are mud volcanoes.